Experimental investigation of the effects of blade geometry on pressure fluctuation and noise of tunnel thrusters. (3rd April 2019) - Yu, Cheng; Dong, Xiao-Qian; Yang, Chen-Jun; Li, Wei; Noblesse, Francis
ABSTRACT: Tunnel thrusters are more vulnerable to cavitation due to the tip clearance flow, blockage effect of the gearbox, and heavy blade loads as compared with open propellers, which makes the problems of structure vibration and radiated noise more serious. Unfortunately, there are few public sources of relevant experimental study. In this context, model experiments have been carried out in the cavitation tunnel of the Shanghai Jiao Tong University to investigate the effects of blade geometry on pressure fluctuation and noise. The experimental results indicate that the traditional 'flat plate' blade is unfavourable for vibration excitation, while unloading towards the tip can effectively reduce both the fluctuating pressure and the noise levels.